Benefícios previdenciários e assistenciais: o idoso e a família - Nogueira, Neuma (2007)
This dissertation was originated by a bursting question: how does the appropriation of the welfare benefits of the elderly institutionalized in Grupo Vida Residência occur? The investigation revealed that these benefits are not used by the elderly, but by their family or friends. The research aimed to investigate the process of concession and usufruct of the benefits. The answers obtained through the interviews made it possible to classify the different ways of appropriation, according to the intentions and motivations of the relatives or the responsible for the elderly. The interviews reveal the relationships that exist behind the scene of the utilization of this resource and the importance it has to the families and to society. In the investigation, it was outstanding how easy it is to circumvent the system. The dissertation was organized in a way to approach progressively to the theme of investigation. Its contribution to gerontology, a typically multi-subject science, is to bring themes such as the social welfare legislation, the evolution of conquered rights, the role of the elderly in this process, the historical path of philanthropy in Brazil and its relations with social assistance and with the State. From a personal point of view, although I have worked with the elderly for a long time, the investigation revealed aspects of the lives of the institutionalized elderly and their families that remained in what I call the silent conspiracy